The resurgence of national development planning: how did we get back here?. Issue 2 (April 2020) - Munro, Lauchlan T.
Abstract : After decades in the political and ideological wilderness, national development planning has made a comeback. The number of countries with a national development plan has doubled since 2006. Given that national development planning has always served various interests and ideologies and that it has always had both political and technical aspects, this article asks, 'how did we get back here?'. This article uncovers the pathways that countries have taken back to national development planning, and outline the various motivations for re-embarking on national development planning. In many cases, an earlier generation of liberal economic policies created both the need and the political space for a new generation of national planning. We explore how the complex interplay of external and internal forces led back to national planning in different types of settings.